GARAP KEBAR IN JAVANESE KARAWITAN - Sugimin, S., (Institut Seni Indoensia Surakarta, 2016)
Garap kebar is one of the treatment on the musical offerings of Javanese musical by using a kebar’s drum pattern presented irama tanggung and dados responsibility to fulfill the musical expression by considering a variety of needs. The emergence of garap kebar on the musical offerings are caused byvarious factors, among which are interpretation of treatment, creativity of artists, and serving functions. There are several options kebar drum pattern that each has a different character, that kebar gambyong, kebar golek, kebar matut, and kebar gecul. Various aspects of forming the musical sense in garap kebar include: musical pattern instrument, rhythm, tempo or laya, and serving functions. Gending who worked kebar containing musical taste sigrak, berag, prenes, and gecul.Keywords: interpretation of treatment , creativity, and offering functionality.